Atorvastatin enhances interleukin-10 levels and improves cardiac function in rats after acute myocardial infarction - Stumpf, Christian; Petzi, Stephan; Seybold, Katrin; Wasmeier, Gerald; Arnold, Martin; Raaz, Dorette; Yilmaz, Atilla; Daniel, Werner; Garlichs, Christoph (Clinical Science, 2009)
LV (left ventricular) remodelling is the basic mechanism of HF (heart failure) following MI (myocardial infarction). Although there is evidence that pro-inflammatory cytokines [including TNF-α (tumour necrosis factor-α) and IL-6 (interleukin-6)] are involved in the remodelling process, only little is known about the role of anti-inflammatory cytokines, such as IL-10. As accumulating evidence has revealed that statins possess anti-inflammatory properties, the aim of the present study was to elucidate the effect of atorvastatin on the modulation of the anti-inflammatory cytokine IL-10 and its effect on LV function in rats with HF subsequent to MI. Rats with MI, induced by permanent LAD (left anterior descending) branch coronary artery ligation, were treated for 4 weeks with atorvastatin (10 mg · kg-1 of body weight · day-1 via oral gavage) starting on the first day after induction of MI. Cardiac function was assessed by echocardiography and cardiac catheterization 4 weeks after MI induction. Membrane-bound and soluble fractions of TNF-α, IL-6 and IL-10 protein, the TNF-α/IL-10 ratio, serum levels of MCP-1 (monocyte chemoattractant protein-1) as well as myocardial macrophage infiltration were analysed. Treatment with atorvastatin significantly improved post-MI LV function (fractional shortening, + 120 %; dP/dtmax, + 147 %; and LV end-diastolic pressure, - 27 %). Furthermore atorvastatin treatment markedly decreased the levels of TNF-α, IL-6 and MCP-1, reduced myocardial infiltration of macrophages and significantly increased myocardial and serum levels of the anti-inflammatory cytokine IL-10. Thus the balance between pro-inflammatory and anti-inflammatory cytokines was shifted in the anti-inflammatory direction, as shown by a significantly decreased TNF-α/IL-10 ratio. Atorvastatin ameliorated early LV remodelling and improved LV function in rats with HF subsequent to MI. Our study suggests that the modulation of the balance between pro- and anti-inflammatory cytokines towards the anti-inflammatory cytokine IL-10 is one salutary mechanism underlying how atorvastatin influences post-MI remodelling and thus improves LV function. © The Authors Journal compilation © 2009 Biochemical Society.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Atorvastatin; Heart failure; Inflammation; Interleukin-10; Myocardial infarction